Preparation and Characterization of Florfenicol-Polyethyleneglycol 4000 Solid Dispersions with Improved Solubility - Ma, Suying; Shang, Xiaojun (Asian Journal of Chemistry, 2012)
Florfenicol/polyethyleneglycol 4000 solid dispersions (FF/PEG4000 SDs) was prepared by the melting and solvent-melting methods. Infrared spectrum and differential thermal analysis were employed to study the physical and chemical properties. Studies of dissolution rate and solubility of florfenicol from solid dispersions were carried out in comparison with corresponding physical mixtures and drug alone. The UV method was developed for determination the concentrations. It was found that the spectra of IR, DTA of the solid dispersions were remarkably different from the florfenicol and physical mixture. Solubility of florfenicol was enhanced for the formation of solid dispersions. The dissolution rate of solid dispersions prepared by solvent-melting method was higher than that of solid dispersion prepared by melting method. The calibration curve was linear with a correlation coefficient r = 0.9999 in the range of 50.0-350.0 μg/mL. PEG4000 is a potential carrier in enhancing the dissolution rate and solubility of florfenicol.